Chrysophyllum albidum mucilage as a binding agent in paracetamol tablet formulations. (2016)
Chrysophyllum mucilage obtained from the fruit of Chrysophyllum albidum (Family Sapotaceae) hasbeen characterised and evaluated as a binding agent in comparison with methylcellulose in paracetamol tabletformulations. Chrysophyllum mucilage was characterized using elemental and proximate analyses as well as material properties. The Heckel and Kawakita plots were used to assess the compressional properties and the tablet properties were evaluated using tensile strength, friability, disintegration and dissolution times. The results showed the presence of calcium, magnesium, potassium, sodium, manganese, iron, copper, zinc and absence of heavy metals from the mucilage. The mucilage exhibited excellent flow and swelling properties, but poor water solubility. The viscosity of chrysophyllum mucilage increased with decrease in temperature in a similar manner with methylcellulose. C. albidum mucilage when used as a binder in paracetamol tablet formulation induced faster onset of plastic deformation and higher amount of total plastic deformation than methylcellulose. The results of the tablet properties showed that the tensile strength, disintegration and dissolution times, increased with increase in binder concentration while friability decreased. Tablets containing chrysophyllum mucilage as binder also had lower tensile strength, disintegration and dissolution times but higher friability values than those containing methylcellulose. However, tablets containing chrysophyllum mucilage at low concentrations conformed to pharmacopeial standard on disintegration indicating its potential usefulness as binder for immediate release tablets. Thus, C. albidum mucilage could be used as an alternative binding agent in pharmaceutical tablets